2022
DOI: 10.3390/photonics10010006
|View full text |Cite
|
Sign up to set email alerts
|

Compression Optical Coherence Elastography for Assessing Elasticity of the Vaginal Wall under Prolapse after Neodymium Laser Treatment

Abstract: Early stages of pelvic organ prolapses are mainly associated with the pelvic floor disfunction as a result of elasticity changes in the connective tissues including the vaginal wall. In this study, for the first time we used a compression optical coherence elastography (C-OCE) method for assessing elasticity of the vaginal wall under prolapse conditions after intravaginal neodymium (Nd:YAG) laser treatment. C-OCE was used for a comparative ex vivo study of vaginal wall average values of stiffness (elastic Youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…It should be noted that CP OCT, in comparison with C-OCE, has greater potential to be used for further, more rapid derivation of 2D or 3D images of the vaginal wall tissue in vivo with higher resolution (~10-15 µm) without additional compression of the tissue and using a reference layer. In addition, compared to our previous C-OCE study [30], the number of study samples was increased, which confirmed our results on the nature of the changes in the collagen bundles in vaginal wall prolapse without and after laser treatment. Our study is also consistent with studies using electron microscopy, in which it was observed that collagen fibrils lost their normal parallel structures in the affected vaginal tissue and also had large gaps between them [52,53].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It should be noted that CP OCT, in comparison with C-OCE, has greater potential to be used for further, more rapid derivation of 2D or 3D images of the vaginal wall tissue in vivo with higher resolution (~10-15 µm) without additional compression of the tissue and using a reference layer. In addition, compared to our previous C-OCE study [30], the number of study samples was increased, which confirmed our results on the nature of the changes in the collagen bundles in vaginal wall prolapse without and after laser treatment. Our study is also consistent with studies using electron microscopy, in which it was observed that collagen fibrils lost their normal parallel structures in the affected vaginal tissue and also had large gaps between them [52,53].…”
Section: Discussionsupporting
confidence: 89%
“…In our previous paper [30] describing quantification of changes in the state of collagen bundles localized in the laminae propria of the same studied groups, C-OCE methods and quantitative morphological analysis of the collagen bundles (local thickness, uniformity and orientation) were used. In the case of vaginal wall prolapse, we observed a statistically significant decrease in tissue stiffness and its increase after Nd:YAG laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations